Model Remaja Putri: Body Image dan Bulimia Nervosa - Anindita, Siti Mutia (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2021)
The physical changes that very fast in teenage girls make they are very care and has high awareness of their body image. Unhealthy body image and it appear to be body image disturbance give negative effects for teenage girls, especially it can be clinical problems such as bulimia nervosa or anorexia nervosa. The purpose of this study is knowing the relationship between body image and tendency to be bulimia nervosa in teenage girl models. This study involved 62 respondents from 20% of total teenage girl population. To measure the body image, we use the MBSRQ measuring instrument developed by Thomas F. Cash (1989) and adapted by Jihan Kemala (2002). Meanwhile, to measure the tendency of bulimia nervosa, researchers made a measuring instrument for individual factors who experiencing bulimia nervosa disorder, there are 13 indicators in the measuring instrument. The researchers using correlation test by Spearmen’s rho correlation. The result of this study aim that there is nl significant negative relationship between body image and tendency of bulimia nervosa in teenage girl model. It means the positive body image in teenage girl model not allowed with decreasing the tendency of bulimia nervosa significantly.